Frequent laboratory abnormalities in CIDP patients. Issue 6 (9th May 2016) - Abraham, Alon; Albulaihe, Hana; Alabdali, Majed; Qrimli, Mohammad; Breiner, Ari; Barnett, Carolina; Katzberg, Hans D.; Lovblom, Leif E.; Perkins, Bruce A.; Bril, Vera
ABSTRACT: Introduction: The role of screening laboratory tests in chronic inflammatory demyelinating polyneuropathy (CIDP) is currently unknown. The objectives of this study are to explore common laboratory test abnormalities in CIDP patients. Methods: CIDP subjects attending the Neuromuscular Clinic between 01/2013 and 12/2014 were evaluated. Demographic data, clinical history, physical examination, and laboratory test results were extracted from their charts. Results: Seventy‐nine charts were reviewed. Mean age was 61 ± 11 years. Most (84%) CIDP patients had laboratory test abnormalities; the most frequent were paraproteinemia (29%) and elevated HbA1C (28%) and creatine kinase (27%). Additional abnormalities included anemia in 19%, and elevated anti‐neutrophil cytoplasmic antibody, erythrocyte sedimentation rate, and urate in 17%, elevated antinuclear antibodies, rheumatoid factor, and thyroid‐stimulating hormone in 11%, and abnormal C3 in 10%. Conclusions: Laboratory test abnormalities were found in most CIDP patients. The most common were paraproteinemia, higher than expected frequency of diabetes, and unexpected CK elevation. Additional abnormalities included anemia, high urate levels, and common biomarkers for vasculitic neuropathies. Muscle Nerve 53 : 862–865, 2016